Load Monitoring With Foucault: Suggestions for the Management of Perceived Exertion in the Elite Sport Context. Issue 4 (21st August 2022) - Paul, Darren; Jones, Luke; Read, Paul
ABSTRACT: Athlete subjective reporting monitoring tools, such as session rating of perceived exertion (RPE), are commonly used to measure internal load. RPE is based on calculation of athletes' rating on the Borg category 1–10 scale multiplied by the exercise duration. Coaches can then use this feedback to ascertain whether the athletes' reported RPE is aligned with their own rating of intended (pre training/competition) or observed exertion (post-training/competition perception of exertion). In this paper, a socio-cultural perspective informed by French philosopher Michel Foucault (14) is used to explore factors that can shape the perceptions and attitudes of the main stakeholders involved in the load monitoring process (the practitioner/coach and the athlete). This approach has led us to suggest that when engaged in load monitoring, there is a need for the coaches or conditioning practitioners to reflect on the impact of and alter their approach to, their daily monitoring protocols. Specifically, how their management of athlete generated data can influence the efficacy of their working relationships and ability to develop athletes in an ethical fashion.